GENESIS OF HYDROCARBONS IN BOTTOM SEDIMENTS OF THE SAKHALIN SHELF - Nemirovskaya I.A.; Moiseichenko G.V.; Blinov Yu.G. (My University, 2003)
Investigations of hydrocarbons in the bottom sediments of the Sakhalin Island Shelf before exploitation of petroleum and natural gas fields have shown their low concentrations. At the place of the hole drilling, increase in concentrations of aliphatic hydrocarbons has been noted. Presence of transformed anthropogeneous petroleum alkanes not detected earlier shows increase in contamination connected with intensification of economic activity in this region. It has been noted that during interpretation of data on levels of petroleum contamination in bottom sediments, it is necessary to notice their lithological type and to take into account existence of natural geochemical background of hydrocarbons. In this case, it is necessary not only to determine hydrocarbon concentrations but also their compositions.